2017
DOI: 10.1002/cssc.201700171
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐Efficient Synthesis of Highly Porous CoCO3 Anodes from Supercritical CO2 for Li+ and Na+ Storage

Abstract: An eco-efficient synthetic route for the preparation of high-performance carbonate anodes for Li and Na batteries is developed. With supercritical CO (scCO ) as the precursor, which has gas-like diffusivity, extremely low viscosity, and near-zero surface tension, CoCO particles are uniformly formed and tightly connected on graphene nanosheets (GNSs). This synthesis can be conducted at 50 °C, which is considerably lower than the temperature required for conventional preparation methods, minimizing energy consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…In addition, our team has demonstrated that SCCO 2 itself can serve as the precursor in the synthesis of a highly porous CoCO 3 /graphene nanocomposite anode for Li + and Na + storage. [ 36 ] The charge–discharge properties were superior to those of the conventionally synthesized CoCO 3 counterpart. To the best of our knowledge, using SCCO 2 to create coating layers on Si particles has not been previously attempted.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our team has demonstrated that SCCO 2 itself can serve as the precursor in the synthesis of a highly porous CoCO 3 /graphene nanocomposite anode for Li + and Na + storage. [ 36 ] The charge–discharge properties were superior to those of the conventionally synthesized CoCO 3 counterpart. To the best of our knowledge, using SCCO 2 to create coating layers on Si particles has not been previously attempted.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the hydrothermal process and solvothermal process, the solubility product, namely K sp , of carbonate or bicarbonate precipitation processes is 1.4 × 10 −13 , presenting a relatively high precipitation efficiency. Furthermore, the precipitation process is widely industrialized in the precursor field for manufacturing the used 3C lithium ion battery to prepare the cobalt oxide, aluminum-doped cobalt oxide, and lithium cobalt oxide due to the fact that the raw materials are cheap and easy to obtain, while the preparation technology is simple and the production efficiency is high [20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…As an anode material for LIBs, graphene exhibits a theoretical specific capacity of 744 mAh g −1 , provided that lithium is bound on both sides of graphene to form Li 2 C 6 . RGO (initial discharge capacities of 540–1600 mAh g −1 at 50 mA g −1 ), modified RGO, and RGO‐based composite materials (such as graphene/Si, graphene/CoCO 3 , and graphene/LiFePO 4 ) may be promising alternatives for high‐performance LIBs. For example, hydrogen‐enriched rGO derived by reduction of double‐oxidized GO in scIPA exhibited a rather high reversible discharge capacity of 1331 mAh g −1 even after 100 cycles at a current rate of 50 mA g −1 , which outperformed thermally reduced GO and scIPA reduced single‐oxidized GO electrodes .…”
Section: Formation and Applications Of 2d Materials Processed By Scfsmentioning
confidence: 99%